Analisis Kehilangan Air Pada Saluran Sekunder Lonrong : Studi Kasus Daerah Irigasi Bendung Bissua Kabupaten Gowa - Riswan Riswan; Burhanuddin Badrun; A. Rumpang Yusuf (Program Studi Teknik Sipil Universitas Bosowa, 2023)
Analysis of water loss in the lonrong secondary channel in the irrigation area of the Bissua weir, Gowa Regency, was guided by Burhanuddin Badrun and A. Rumpang Yusuf . The existing irrigation system in the Bissua Dam area began to be built in 2001 and completed in 2004 which is located in Towata Village, North Polongbangkeng District, Takalar Regency, South Sulawesi .This study is to analyze the efficiency and water loss in the Lonrong Secondary irrigation network, Takalar Regency. The study was conducted on a secondary channel. Efficiency and water loss were analyzed using the Inflow – Outflow method. The data used in this analysis is primary data in the form of flow velocity data with a current meter for secondary channels. The flow velocity obtained according to measurements in the upstream secondary is on average 0.37 m/s, while for the downstream the average is 0.167 m/s. For the upstream discharge it is 39,555 m3 / second and for the downstream it is 32,461 m3 / second. The overall water loss in the secondary irrigation network is 7,094 m 3 /second on average